Difficulties in Thought, Language and Communication: A Cross-Sectional Study of Psychiatric People in Bangladesh - Rahman, Mizanur; Siddik, H.M Abubakar; Hasan, Md Zobaer; Ferdous, Jannatul; Alam, Masud; Islam, Md Saiful; Islam, Md Fakhrul (International Journal of Medical and Health Sciences Research, 2021)
People with Psychiatric disorder (PD) have difficulties in their thought, language and communication skills. In Bangladesh, the frequency of mental disorders is 12.2%, where females are more vulnerable than the male. The main purpose of this study was to find out the thought, language and communication aspects among psychiatric population in Bangladesh. A cross-sectional survey was conducted to meet the study aim, and the data from 70 participants with different types of psychiatric disorder were collected from a specialized mental health hospital in Bangladesh. The participants were between 18 to 65 years old, where the ratio of the male and female was almost equal. A significant (p-value=0.006) relationship was found between language disorder (incoherence) and different types of psychiatric disorder. Professionals, working with psychiatric population need to remain alert to the presence of those issues and refer to appropriate specialists that will increase the wellbeing quality of people with Psychiatric disorder (PD) as well as decrease morbidity.